2018
DOI: 10.1038/s41419-018-0577-y
|View full text |Cite
|
Sign up to set email alerts
|

microRNA-501-3p suppresses metastasis and progression of hepatocellular carcinoma through targeting LIN7A

Abstract: Increasing numbers of evidences have demonstrated that microRNAs (miRNAs) are implicated in metastasis and progression of hepatocellular carcinoma (HCC). However, their detailed expression levels and actual functions in HCCs have not been fully clarified yet. Results from our recent study revealed that some miRNAs were particularly related to metastasis of HCCs. As one of these newly found miRNAs, miR-501-3p showed to highly involve into metastatic process of HCCs. Here we reported that the expression of miR-5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 35 publications
1
30
0
Order By: Relevance
“…Previously, LIN7A is reported to be associated with the development of breast cancer (Gruel et al, ). Recently, Luo et al () also showed that LIN7A promotes liver cancer cell proliferation and metastasis. The specific role of LIN7A in ovarian cancer has not been revealed.…”
Section: Discussionmentioning
confidence: 95%
“…Previously, LIN7A is reported to be associated with the development of breast cancer (Gruel et al, ). Recently, Luo et al () also showed that LIN7A promotes liver cancer cell proliferation and metastasis. The specific role of LIN7A in ovarian cancer has not been revealed.…”
Section: Discussionmentioning
confidence: 95%
“…MiRNAs, including miR-122, miR-192, miR-21, miR-223, miR-26a, miR-27a and miR-80, provided a high diagnostic accuracy of hepatitis B virus-related hepatocellular carcinoma [43]. Moreover, microRNA-501-3p could suppress metastasis and progression of hepatocellular carcinoma through targeting Lin-7 homolog A (LIN7A) [44]. Extracellular miRNA have been already detected in cell-exported exosomes.…”
Section: Extracellular Rna Functionmentioning
confidence: 99%
“…miR-501-3p inhibits migration, proliferation and EMT of HCCLM3 and PLC/PRF/5 HCC cells as shown by gain and loss of function experiments (178). The incidence of lung metastasis of HCCLM3 transfected with miR-501-3p cells was reduced in comparison to control cells in an orthotopic mouse model (178). LIN7A homolog A (LIN7A) was identified as a target of miR-501-3p (178).…”
Section: Mirs-137 and Mir-612 Mir-137 (mentioning
confidence: 99%
“…The incidence of lung metastasis of HCCLM3 transfected with miR-501-3p cells was reduced in comparison to control cells in an orthotopic mouse model (178). LIN7A homolog A (LIN7A) was identified as a target of miR-501-3p (178). It was shown that LIN7A mediates the effects of miR-501-3p in vivo (178).…”
Section: Mirs-137 and Mir-612 Mir-137 (mentioning
confidence: 99%